2020
DOI: 10.1177/0888325420937773
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Welfare Deservingness of Single Mothers: Public Image and Deservingness Perceptions in Hungary

Abstract: The literature on single mothers’ welfare deservingness is dominated by analyses carried out in Anglo-Saxon countries. Those analyses tend to point to an undeserving public image of single mothers. This negative perception is often explained by the identity gap between middle-class voters and poor single mothers, which is partly fuelled by conservative family values in mainstream society. This study investigates the issue in Hungary, where the government has strongly promoted traditional family ideals and sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 16 publications
1
6
0
1
Order By: Relevance
“…Powerful hybrids of deservingness criteria are also used in both debates. Many of them are identical to those found by other researchers, such as ‘the deserving refugee’ (Nielsen et al , 2020) or ‘lazy, non-working mother living off welfare’ (Herke, 2020). My study also revealed other amalgams, such as the figure of ‘Poles’ needs taking priority,’ which turned out to be a salient mix of identity and need criteria, the application of which results in the full denial of refugees’ deservingness.…”
Section: Conclusion and Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…Powerful hybrids of deservingness criteria are also used in both debates. Many of them are identical to those found by other researchers, such as ‘the deserving refugee’ (Nielsen et al , 2020) or ‘lazy, non-working mother living off welfare’ (Herke, 2020). My study also revealed other amalgams, such as the figure of ‘Poles’ needs taking priority,’ which turned out to be a salient mix of identity and need criteria, the application of which results in the full denial of refugees’ deservingness.…”
Section: Conclusion and Discussionsupporting
confidence: 83%
“…This was done in Poland, which employs a hybrid welfare state model and has witnessed contentious identity politics (Lendvai-Bainton and Szelewa, 2020), potentially increasing the complexity and polarisation of opinions on deservingness (Gugushvili and van Oorschot, 2020). This analysis contributes to a growing body of qualitative research about how in practice people make deservingness claims (Herke, 2020; Heuer and Zimmermann, 2020; Laenen, 2020; Nielsen et al , 2020; Osipovic, 2015).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In their recent study Heuer and Zimmerman (2020) found that respondents emphasize identity (as well as the need and social investment) as the main deservingness criteria that are applied with regards to families. People who stereotypically violate the dominant social norms, for example single mothers, are more likely to be found undeserving (Herke, 2019).…”
Section: Identitymentioning
confidence: 99%